2015
DOI: 10.1007/s40273-015-0361-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Economic Burden of Pulmonary Arterial Hypertension

Abstract: The economic burden of patients with PAH is substantial, while the paucity of comprehensive country-specific evidence in this area and the lack of reports on indirect costs of PAH warrant researchers' concern, especially in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 56 publications
4
28
0
Order By: Relevance
“…The mean, annual, total direct healthcare costs of Group 3 PH patients to payers were $44,732 (approximately $3,728 per month). Other studies have estimated the economic burden of Group 1 PH (PAH) patients and of Group 4 PH (CTEPH) patients using large claims databases [916]. Differences in data sources, eligibility criteria, methodology, and analytical methods among studies limit a direct comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean, annual, total direct healthcare costs of Group 3 PH patients to payers were $44,732 (approximately $3,728 per month). Other studies have estimated the economic burden of Group 1 PH (PAH) patients and of Group 4 PH (CTEPH) patients using large claims databases [916]. Differences in data sources, eligibility criteria, methodology, and analytical methods among studies limit a direct comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found significant healthcare resource utilization and economic burdens associated with WHO Group 1 PH (pulmonary arterial hypertension, PAH) and Group 4 PH (chronic thromboembolic pulmonary hypertension, CTEPH) [916]. However, there is no similar study for Group 3 PH patients as a whole in the US medical literature.…”
Section: Introductionmentioning
confidence: 99%
“…Sildenafil was reported to be cost-effective and associated with lower costs and higher efficacy. (9) In our institution, the cost of PDE5 inhibitor therapy is estimated to be about SGD 500-1,000 per patient per month prior to funding. For patients on combination therapy, pharmacy costs are cumulative.…”
Section: Discussionmentioning
confidence: 99%
“…The economic burden of patients with PAH is noteworthy. Doubtless, the cost for drugs represents the main determinant of the whole expenditure, although the indirect costs for the treatment of patients with PAH are not clearly defined, as suggested by recent surveys (91,92). These reviews showed that the health care costs for treating PAH in USA varied widely from 2,476$ to 11,875$ per patient per month.…”
Section: Economical Sustainability Of Rehabilitation Programs In Pahmentioning
confidence: 99%